TARBIYATUL QULUB MELALUI DZIKIR - Haromaini, Ahmad; Rachman, Abdul; Al-Fahmi, Faiz Fikri (Universitas Islam Syekh Yusuf, 2021)
Abstract Humans were created with a clear mission. According to the expert commentators, there are three missions carried out by humans as Allah Almighty's creatures on earth, the mission of worshiping, the caliph, playing a role in prospering the earth. Then he was given some potential. One of these potentials is the heart